Legal Protection for Medical Research Doctors Concerning Human Research Subjects - Uswatun Khasanah; Sutarno Sutarno; Andika Persada Putera (Jurnal Indonesia Sosial Sains, 2025)
Medical research or health research involving humans as research subjects has great potential in the development of medical science and technology. However, this research also poses risks to research subjects. Therefore, legal protection for medical researchers is very important. This research aims to analyze the legal basis and regulations applicable in Indonesia to protect medical researchers and humans as research subjects. The research method used is normative juridical with a statute approach and a conceptual approach. The results of the research show that Indonesia has several laws and regulations governing health research, but the material that specifically discusses the legal protection of medical researchers is not explicitly mentioned in the regulations. In the future, it is expected that medical researchers will receive balanced attention, so as to provide peace of mind for medical researchers to work, so that the development of science in the field of health and technology is more advanced and provides many benefits for the medical world.